Pola Bakteri Aerob pada Sampel Sputum dan Uji Sensitivitas Antibiotik Pasien Rawat Inap di RSU Gmim Pancaran Kasih Manado - Vanessa Caitlin Euginia Kho; Heriyannis Homenta; Olivia Amelia Waworuntu (Jurnal Syntax Admiration, 2025)
Aerobic bacteria can act as pathogens and cause infections, including respiratory tract infections (RTIs). Patients with RTIs generally present with symptoms of cough accompanied by mucus. There are various types of bacteria in sputum, so sputum analysis is crucial and representative for detect the cause of infection. Bacterial infections can be treated with antibiotics. However, misuse of antibiotics has led to increased resistance, which exacerbates treatment challenges and increases mortality rates. This study aims to identify bacterial patterns and antibiotic sensitivity in sputum sampels of inpatients at GMIM Pancaran Kasih General Hospital in Manado. This study used a descriptive obervasional study design with with a cross-sectional approach. Bacteria were identified using Gram staining and biochemical tests, then antibiotic sensitivity test using the disk diffusion method and Vitek. The study found Gram-positive bacteria, including Staphylococcus spp. (62.50%), Bacillus spp. (12.50%), and Streptococcus spp. (6.25%), and Gram-negative bacteria, specifically Sphingomonas paucimobilis (18.75%). The bacteria are sensitive to Meropenem and Gentamicin (100%), but resistant to Ampicillin and Aztreonam (100%). The most common bacteria found in sputum were Staphylococcus spp., which were sensitive to Meropenem and Gentamicin but resistant to Ampicillin and Aztreonam.